Professional level of the interview genre in morning entertainment programs and its modern audience (Herald of Journalism, 2023)
The reason for writing the article was the idea to define the function of the interview genre as a way of communication between the media and the public by studying the professional level and the target audience in morning entertainment programs.The aim of the study is to analyze the professional level and target audience of the interview genre, the differences and similarities between modern and traditional interviews in the domestic media space, in particular, on national television, as well as on the Internet.The scientific and practical significance of the work is in the assessment the special nature of the interview genre in the information age, transformation and modernization in the genre of TV interviews, modern technologies of TV interviews, the scope of modern applications, including the progress of interviews in morning entertainment live programs, information activity and motivational benevolent impact of feedback from the target audience, the rating indicator of morning entertainment programs and online interviews.According to the research methodology, the methods of presentation, review, comparison, argumentation, analysis, systematization, description, grouping, summing up were used.The main results of the scientific research are reflected in the conclusions substantiated by grouping and systematizing the types and forms of interviews that have appeared in the trends of the interview genre, based on the opinions of scientists who previously studied the interview genre, moreover, the analysis of the professional image of the interviewees, typical shortcomings within the interview genre.The importance of the research work lies in the fact that new areas of application of the interview genre that have not been studied before, are specially considered and systematized on a scientific and theoretical basis.The practical significance of the results lies in the fact that this work can be used as an auxiliary tool for journalists using the interview genre in the framework of professional activity, and for university teachers from journalism specialty.Keywords: dialogue-interview, monologue-interview, modern technologies of TV interview, target audience of TV interview, transformation and modernization of TV interview genre